A spectroscopy-based methodology for rapid screening and characterization of phytochrome photochemistry in search of Pfr- favoured variants - Antelo, Giuliano Tomás (2020)
Phytochromes are photosensitive proteins with a covalently bound open-chain chromophore that can switch between two principal states: red-light absorbing Pr and far-red light absorbing Pfr. Our group has previously shown that the bacteriophytochrome from Xanthomonas campestris pv. campestris (XccBphP) is a bathy-like phytochrome that uses biliverdin IXα as a co-factor and is involved in bacterial virulence (Bonomi H.R. et al., 2016; Otero L.H. et al., 2016). To date, the XccBphP crystal structure could only be solved in the Pr state (Klinke S. et al., 2014; Otero L.H. et al., 2016), while the structure of its Pfr state remains elusive. The aims of this work were to develop an efficient screening methodology for the rapid characterization and to identify XccBphP variants that favour the Pfr form. The screening approach developed here consists in analyzing the UV-Vis absorption behaviour of clarified crude extracts containing recombinant phytochromes. This strategy has allowed us to quickly explore over a hundred XccBphP variants, characterize multiple variants and identify Pfr-favoured candidates. The high-quality data obtained enabled not only a qualitative, but also a quantitative characterization of their photochemistry. This method could be easily adapted to other phytochromes or other photoreceptor families.